Identities, Boundaries, and Accounts of Women Methamphetamine Users. (2nd January 2016) - Copes, Heith; Leban, Lindsay; Kerley, Kent R.; Deitzer, Jessica R.
Abstract : Drug users often define themselves as functional users and depict others as dysfunctional (i.e. junkies). Previous research on the social identities of drug users has focused on the symbolic boundaries they create to distance themselves from stigmatized others. Investigators have yet to focus on how users account for their own boundary violations. Here, we examine the narratives of 30 former women methamphetamine (meth) users to determine how they make distinctions between functional and dysfunctional meth users (i.e. "meth heads"). The distinctions they make are based on users' abilities to maintain control of their lives and to hide their use from outsiders. Those who saw themselves as functional but who engaged in behaviors inconsistent with this image accounted for these behaviors to maintain desired identities. We show the complexity of drug users' identities and illustrate how anti-drug campaigns that provide grotesque caricatures of drug users may prolong drug using careers.